The feral horse foot. Part A: observational study of the effect of environment on the morphometrics of the feet of 100 Australian feral horses. Issue 1 (21st September 2012) - Hampson, BA; de, MA; Mills, PC; Pollitt, CC
<x xml:space="preserve">Abstract</x> Aim To better understand the morphology of, and the effect of different travel patterns and varying substrate environments on, the feral horse foot to better manage the feet of domestic horses. Methods The left forefeet of 20 adult feral horses from each of five geographically separated populations in Australia (n = 100) were investigated. Populations were selected on the basis of substrate hardness under foot and the amount of travel typical for the population. Feet were radiographed and photographed and 40 morphometric measurements of each foot were obtained. Results Of the 40 parameters, 37 differed significantly (P < 0.05) among the populations, which suggested that substrate hardness and travel distance have an effect on foot morphology. Harder substrates and longer travel distances were associated with short hoof walls and minimal hoof wall flaring. Softer substrates and moderate travel distances were associated with long flared walls, similar to that of typical untrimmed feet of domestic horses. Conclusions The morphology of the feral horse foot appeared to be affected by the distance travelled and by the abrasive qualities and mechanical properties of the substrate under foot. There were marked differences in some conformation parameters between the feral horses in the current study and domestic horses in previous studies. Although the conformation of the feral horse foot may have some prescriptive value, concerns regarding abnormal foot anatomy warrant further investigation.